2022
DOI: 10.3390/vaccines10101726
|View full text |Cite
|
Sign up to set email alerts
|

Poliovirus Immunity among Children Aged 6–11 and 36–48 Months in 14 Polio High-Risk Provinces of Afghanistan: A Health-Facility-Based Study

Abstract: Afghanistan is one of two countries where wild poliovirus (WPV) type 1 remains endemic. We conducted a facility-based cross-sectional survey of antipoliovirus antibodies in children in 14 provinces of Afghanistan. The provinces were selected based on programmatic priorities for polio eradication. Children aged 6–11 and 36–48 months attending outpatient clinics were enrolled in the study. We collected venous blood, isolated serum, and conducted neutralization assays to detect poliovirus neutralizing antibodies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In 2017, two similar studies were carried out in Afghanistan. One study was conducted in Kandahar province ( 25 ), and the other was a facility-based study conducted in 14 polio high-risk provinces of Afghanistan ( 26 ). Both studies found high prevalence of PV1 and PV3 in children of both age brackets (aged between 6 to 11 months and between 36 to 48 months), with low prevalence of PV2 in the younger age group compared to the older age group.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, two similar studies were carried out in Afghanistan. One study was conducted in Kandahar province ( 25 ), and the other was a facility-based study conducted in 14 polio high-risk provinces of Afghanistan ( 26 ). Both studies found high prevalence of PV1 and PV3 in children of both age brackets (aged between 6 to 11 months and between 36 to 48 months), with low prevalence of PV2 in the younger age group compared to the older age group.…”
Section: Discussionmentioning
confidence: 99%